Dynamic modelling of the climate change impact in the Conchos River basin water management / Modelación dinámica de los efectos del cambio climático en gestión del agua en la cuenca del rÃo Conchos - Martínez Austria, Polioptro F.; Vargas Hidalgo, Alberto; Patiño Gómez, Carlos (Tecnología y ciencias del agua, 2019)
In the last decades there have been some deficits in water deliveries that Mexico must make to the United States under the Water Treaty between the two countries. Population growth and the effects of climate change make possible foresee that the difficulties will increase in the future. This text analyzes the observed changes in rainfall in the basin, and a dynamic model is developed to estimate the effects of climate change on the water balance of the Conchos river basin, which contributes 87% of the amount of water established as Mexicans commitments in the Treaty. The results of three scenarios are shown and the effects on water availability in the basin are exposed. A sensitivity analysis is presented, with the Montecarlo method, regarding the main effects of climate change in the basin. To analyze the effects on irrigation, the main use of water in the basin, a adaptive dynamic model and its results are also presented. Finally, the expected effects on future availability are concluded, and general recommendations are made for adaptation to climate change.